Malta : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 1999)
This 1999 Article IV Consultation highlights that real GDP growth in Malta in 1997 and 1998 continued the declining trend. The contribution to demand from net exports offset weaker growth of real consumption and investment. Export volumes rose by 3 percent and 5 percent in 1997 and 1998, respectively, with machinery exports performing particularly strongly, while import volumes contracted in 1997 by 4 percent before rising by 2 1\2 percent in 1998. Import behavior mirrored that of domestic demand, which slowed as the growth of household consumption fell to below 1 percent in 1997 and 1998.